2012
DOI: 10.1097/jto.0b013e3182653d31
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Polymorphisms and Treatment Outcomes of Patients with Malignant Mesothelioma Treated with Gemcitabine-Platinum Combination Chemotherapy

Abstract: Our results support the hypothesis that DNA repair gene polymorphisms, particularly XRCC1 Arg399Gln, may modify the response to gemcitabine-platinum combination chemotherapy and, for the first time, show this effect in patients with MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…In previous studies, we have identified some polymorphisms that influence MPM treatment with gemcitabine and cisplatin 26,43,44. Our present results show for the first time that MTHFD1 , ABCC2 , and SLCO1B1 polymorphisms may play an important role in PMX treatment response in patients with MPM.…”
Section: Discussionsupporting
confidence: 63%
“…In previous studies, we have identified some polymorphisms that influence MPM treatment with gemcitabine and cisplatin 26,43,44. Our present results show for the first time that MTHFD1 , ABCC2 , and SLCO1B1 polymorphisms may play an important role in PMX treatment response in patients with MPM.…”
Section: Discussionsupporting
confidence: 63%
“…The selection of genetic and clinical variables was based on results of our previous studies where pathway-based approach was used to identify factors influencing tumor response, PFS or OS in Slovenian MM patients11121314. In this study genotyping for all polymorphisms in gemcitabine, pemetrexed and cisplatin metabolism, transport and drug target genes and DNA repair pathways significantly associated with treatment outcome in previous studies was extended to all patients.…”
Section: Methodsmentioning
confidence: 99%
“…So far, no target mutations were identified in MM that could guide targeted treatment. MM treatment outcome was associated with clinical characteristics10 and genetic variability in drug transport, metabolism and target genes and DNA repair pathways11121314.…”
mentioning
confidence: 99%
See 2 more Smart Citations